Effect of estradiol on the course of ovalbumin sensitization in guinea pigs - Wan You; Weng Shi-Ai (Acta Pharmacologica Sinica, 2016)
The latent period of ovalbumin (Ova)-induced asthma in Ova-sensitized guinea pigs was shorter in the ovariectomized animals with sc estradiol (E2) 400 or 50 micrograms.d-1 x 14 d and in animals with intact ovary (84 +/- 35, 82 +/- 33, and 100 +/- 32 s, respectively) than in the ovariectomized animals (140 +/- 29 s) (P < 0.05). The histamine (His) content of the lungs and His released from lungs under Ova challenge in vitro increased in the group of ovariectomy with sc E2 50 micrograms.d-1 x 14 d as compared with those without sc E2 (56 +/- 9 and 47 +/- 11 ng/g wet weight vs 44 +/- 10 and 36 +/- 11 ng/g wet weight) (P < 0.05). However, the pD2 values of the contraction of isolated tracheal strips induced by His and those of the relaxation by isoproterenol (Iso) were not affected. These findings suggest that the strengthened effect of E2 on the sensitization may be related to the content and the release of lung His in guinea pigs.